Ein kosmopolitischer Patriot: Franz Liszt und Ungarn - Redepenning, Dorothea (Osteuropa, 2011)
Vom Beginn seiner Virtuosenlaufbahn bis an sein Lebensende verstand sich Franz Liszt als Botschafter der ungarischen Kultur. Zugleich verfocht er Goethes Idee einer Weltliteratur, die er auf die Musik übertrug. Nationales Denken und Weltbürgertum waren ihm zwei Seiten einer Medaille - ein Standpunkt, der Ende des 19. Jahrhunderts immer unpopulärer wurde. From the start of his virtuoso career until his death, Franz Liszt saw himself as an ambassador of Hungarian culture. At the same time, he defended Goethe's idea of a world literature, which he projected onto music. National thinking and global citizenship were for him two sides of the same coin, a position that was becoming increasingly unpopular at the end of the 19th century.